2006
DOI: 10.2334/josnusd.48.47
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor in saliva is a potential marker of symptomatic periodontal disease

Abstract: Evidence has been emerging that hepatocyte growth factor (HGF) -a pluripotential regenerative cytokine -is a key factor in the pathogenesis and progression of periodontal disease, mostly through its over-stimulation of gingival epithelial cell growth and impairment of the regeneration of collagenous structures. We measured the levels of immunoreactive HGF in unstimulated whole mixed saliva from 26 patients referred for treatment of periodontal disease, and from 20 healthy subjects. HGF was detected in all sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Exceptionally, 3 independent studies demonstrated significant association of salivary HGF with periodontitis [119122] which is consistent with similar data analysing GCF [123]. In terms of function, HGF is known to be involved in dental development [124] but, significantly, HGF is secreted by gingival fibroblasts and HGF secretion is regulated by cytokines and bacterial products; it has been hypothesised that HGF may mediate epithelial apical migration in periodontitis [124, 125].…”
Section: Protein Biomarkers Of Periodontitis: Candidate Protein Stsupporting
confidence: 62%
“…Exceptionally, 3 independent studies demonstrated significant association of salivary HGF with periodontitis [119122] which is consistent with similar data analysing GCF [123]. In terms of function, HGF is known to be involved in dental development [124] but, significantly, HGF is secreted by gingival fibroblasts and HGF secretion is regulated by cytokines and bacterial products; it has been hypothesised that HGF may mediate epithelial apical migration in periodontitis [124, 125].…”
Section: Protein Biomarkers Of Periodontitis: Candidate Protein Stsupporting
confidence: 62%
“…HGF is also a healing factor, with cytoprotective effects in conditions associated with inflammatory diseases, including periodontitis. A number of studies demonstrated that HGF levels were elevated in patients with chronic periodontitis [ 23 , 24 ]. However, despite high concentrations, HGF may appear in a form with reduced biological activity at local inflammation sites [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In periodontitis, the production of HGF is induced by various factors derived from the host, such as inflammatory cytokines and bacterial components. Studies have shown a correlation between the number of deep periodontal pockets and the salivary levels of HGF [ 31 , 32 ]. In the present study, a significantly higher level of salivary HGF was found in smokers with periodontitis and nonsmokers with periodontitis compared to the control group.…”
Section: Discussionmentioning
confidence: 99%